2018
DOI: 10.3847/1538-4357/aaa9bb
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Abundances in the Leading Arm of the Magellanic Stream

Abstract: The Leading Arm (LA) of the Magellanic Stream is a vast debris field of H I clouds connecting the Milky Way and the Magellanic Clouds. It represents an example of active gas accretion onto the Galaxy. Previously only one chemical abundance measurement had been made in the LA. Here we present chemical abundance measurements using Hubble Space Telescope/Cosmic Origins Spectrograph and Green Bank Telescope spectra of four AGN sightlines passing through the LA and three nearby sightlines that may trace outer fragm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 86 publications
7
37
2
Order By: Relevance
“…Our study confirms earlier results on the global metal abudance of LA II (Lu et al 1998;Fox et al 2018) and provides new information on the dust properties and physical conditions in the gas, further constraining of the origin of the LA and its evolution.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study confirms earlier results on the global metal abudance of LA II (Lu et al 1998;Fox et al 2018) and provides new information on the dust properties and physical conditions in the gas, further constraining of the origin of the LA and its evolution.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of the COS G130M data of NGC 3783 presented in Fox et al (2018) yields a slightly lower S ii column density than our analysis of the STIS E140M data (COS: log N (S ii) = 14.41 ± 0.12; STIS: log N (S ii) = 14.57 ± 0.03), although both studies use the same S ii line at 1253.8Å. In Fig.…”
Section: Comparison Between Hst/stis and Hst/cos Datacontrasting
confidence: 49%
See 2 more Smart Citations
“…A number of HST studies have found that the MS has a mean metallicity of [Fe/H] ≈ −1 dex across its length (Fox et al 2010(Fox et al , 2013b, although there is evidence for a more metal-rich component (Richter et al 2013;Fox et al 2013b). The Magellanic Bridge, the gas between the MCs, also has a metallicity of ≈ −1 (Lehner et al 2008) as does the LA (Lu et al 1998;Fox et al 2018;Richter et al 2018). The consistency in the metallicities for these distinct gaseous features that lead, trail, and connect the MCs suggests that they share a common originating system: the MCs, themselves.…”
Section: Introductionmentioning
confidence: 95%